Twostriped Walkingstick, Anisomorpha buprestoides (Stoll) (Insecta: Phasmatodea: Pseudophasmatidae) - Michael C. Thomas (EDIS)
The most common stick insect in Florida is Anisomorpha buprestoides (Stoll), the so-called twostriped walkingstick. Other names applied to it and to stick insects in general include devil's riding horse, prairie alligator, stick bug, witch's horse, devil's darning needle, scorpion, and musk mare (Caudell 1903). The last common name is particularly apt as this species is capable of squirting a strong-smelling defensive spray that is painfully irritating to the eyes and mucous membranes (Gray 1835, Meinwald et al. 1962, Eisner 1965, Stewart 1937, Hatch et al. 1993, Paysse et al. 2001, Dziezyc 1992). Several recent inquiries about such incidents prompted the preparation of this circular. This document is EENY-314 (originally published as DPI Entomology Circular No. 408), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2003.